Regional trading arrangements and trade regime bias : theory and some evidence for the EC and CARICOM - Milner, Chris (Univ. of Nottingham. Centre for Research in EconomicDevelopment and International Trade NottinghamGB, 1992)
Seeks to identify the nature and determinants of trade regime bias in the presence of geographically discriminatory tariffs (using the tools of customs union analysis), and to quantify and compare the trade regime bias induced by membership of a regional grouping in the case of CARICOM and the EC.